CORNELIA DE LANGE SYNDROME: A CASE REPORT - Babikir, Haydar E. (مجلة الجزيرة للعلوم الصحية; مجلد 7 عدد 2 (2011), 2011)
Cornelia de Lange syndrome is a developmental disorder that affects many parts of the body. The first ever documented case was in 1916 by W. Brachmann followed up by Cornelia de Lange , a Dutch pediatrician, in 1933 after whom the disorder has been named. 1,2